2013
DOI: 10.4104/pcrj.2013.00005
|View full text |Cite
|
Sign up to set email alerts
|

A scoring algorithm for predicting the presence of adult asthma: a prospective derivation study

Abstract: Background: To predict the presence of asthma in adult patients with respiratory symptoms, we developed a scoring algorithm using clinical parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…Obstructive lung disease. Ten prospective observational studies, one retrospective observational study, and one cross-sectional study included patients with diagnosis of chronic obstructive lung disease (COPD) or asthma and compared auscultation with spirometry for the detection of airway obstruction [23][24][25][26][27][28][29][30][31][32][33][34] . The results listed Logeart et al 16 Chen et al 20 HPT Retrosp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obstructive lung disease. Ten prospective observational studies, one retrospective observational study, and one cross-sectional study included patients with diagnosis of chronic obstructive lung disease (COPD) or asthma and compared auscultation with spirometry for the detection of airway obstruction [23][24][25][26][27][28][29][30][31][32][33][34] . The results listed Logeart et al 16 Chen et al 20 HPT Retrosp.…”
Section: Resultsmentioning
confidence: 99%
“…Tomita et al 34 www.nature.com/scientificreports www.nature.com/scientificreports/ in Table 2, show a poor diagnostic accuracy of auscultation for OLD. Table 3 shows that for the diagnosis COPD abnormal, decreased or absent breath sounds have a LR + of 4.3, with five available studies, and wheezes have a LR + of 3.6, with ten available studies (see also Supplementary Figure 4).…”
Section: Pc Feb-jun 2001mentioning
confidence: 99%
“…Eight articles from seven studies met the review criteria and were included. 1421
Fig. 1Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) flow diagram
…”
Section: Resultsmentioning
confidence: 99%
“…This study also found that certain subgroups are at greater risk of hospitalisation. It may be that those at risk of RTI-related hospitalisation could be defined in greater detail, thus enabling the development of a symptom-based scoring algorithm modelled on algorithms that already exist for many other conditions [11,25,26]. However, symptoms are not well recorded in routine records.…”
Section: Implications For Clinical Practice and Researchmentioning
confidence: 99%